2004
DOI: 10.1073/pnas.0301964101
|View full text |Cite|
|
Sign up to set email alerts
|

Retinoblastoma protein functions as a molecular switch determining white versus brown adipocyte differentiation

Abstract: Adipocyte precursor cells give raise to two major cell populations with different physiological roles: white and brown adipocytes. Here we demonstrate that the retinoblastoma protein (pRB) regulates white vs. brown adipocyte differentiation. Functional inactivation of pRB in wild-type mouse embryo fibroblasts (MEFs) and white preadipocytes by expression of simian virus 40 large T antigen results in the expression of the brown fat-specific uncoupling protein 1 (UCP-1) in the adipose state. Retinoblastoma gene-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
253
3
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 251 publications
(284 citation statements)
references
References 38 publications
21
253
3
7
Order By: Relevance
“…Mechanisms of intracellular signaling sensitive to enhanced oxidative stress and altered energy metabolism (AMP-kinase, Sirt1, CHOP-10 and others) may convey these alterations into changes in overall adipocyte function and gene expression thus leading to impaired adipocyte differentiation, altered release of regulatory adipokines and enhanced apoptosis. 46 Acquisition of this proliferative status in association with some brown fat-like features is consistent with observations that inhibition of the activity of the retinoblastoma protein, a repressor of cell proliferation, drives pre-adipocytes to a brown versus a white phenotype 47 and may be associated with some intrinsic properties of brown adipocyte precursors to proliferate under physiopathological stimuli. In fact, brown adipose tissue in rodents is characterized by a capacity for dramatic enlargement, including cell proliferation, in response to external signals associated with thermogenic requirements.…”
Section: Lipomatosis In Hals Reveals a Potential For Brown Adipocyte supporting
confidence: 72%
“…Mechanisms of intracellular signaling sensitive to enhanced oxidative stress and altered energy metabolism (AMP-kinase, Sirt1, CHOP-10 and others) may convey these alterations into changes in overall adipocyte function and gene expression thus leading to impaired adipocyte differentiation, altered release of regulatory adipokines and enhanced apoptosis. 46 Acquisition of this proliferative status in association with some brown fat-like features is consistent with observations that inhibition of the activity of the retinoblastoma protein, a repressor of cell proliferation, drives pre-adipocytes to a brown versus a white phenotype 47 and may be associated with some intrinsic properties of brown adipocyte precursors to proliferate under physiopathological stimuli. In fact, brown adipose tissue in rodents is characterized by a capacity for dramatic enlargement, including cell proliferation, in response to external signals associated with thermogenic requirements.…”
Section: Lipomatosis In Hals Reveals a Potential For Brown Adipocyte supporting
confidence: 72%
“…Thus, the sympathetic nervous system seems to play a fundamental role in the plasticity of the adipose organ and a positive correlation has recently been shown between the density of noradrenergic parenchymal fibres and the density of brown adipocytes in the adipose organ under different environmental temperatures (15) . Figure 6 summarizes the morphological and immunohistochemistry stages of the physiological and reversible transdifferentiation of white into brown adipocytes, which is supported by data from a number of different research groups (48)(49)(50)(51)(52)(53)(54) .…”
Section: The Reversible Transdifferentiation Phenomenonsupporting
confidence: 58%
“…26 In addition to C/EBPs, as shown in the present studies, JDP2 might be a target of such signal networks. Other report suggested that the absence of retinoblastoma protein (Rb) switched the differentiation of MEF cells from white to brown adipocytes, 27 suggesting that the differentiation of WT MEFs to adipocytes is a good model for white adipocyte differentiation but not brown adipocyte differentiation. We also observed that PGC-1a, a marker of brown adipocyte, was not induced after induction of adipocyte differentiation in Jdp2 À/À MEFs and WT MEFs (data not shown).…”
Section: Discussionmentioning
confidence: 99%